2010
DOI: 10.1111/j.1472-4642.2009.00635.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of significant shorebird areas: thresholds and criteria

Abstract: Aim  Conservation managers designate significant areas for shorebirds based on imperfect data. Significant wetlands for migratory shorebirds have usually been identified on the basis of whether they exceed certain thresholds, defined either by total abundance (usually 20,000 waterbirds) or percentage of a population (usually 1.0%). We evaluate the performance of existing criteria and determine if lowering thresholds would improve shorebird conservation without adding unreasonable numbers of significant sites. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…This suggested that the interaction of coarse environmental variables can reflect population trends measured in other ways, and that one can begin to make inferences about population trends across remote interior Australia using modelling approaches such as those developed here. For shorebirds, these models helped improve our estimates of total population size, which has been the foundation on which abundance thresholds to identify important habitats have been based (DEH, 2006;Clemens et al, 2010). Model predictions also indicated that over the decades some species experience periods of far greater contractions in suitable habitat than others, consistent with other recent work (Runge et al, 2015a).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This suggested that the interaction of coarse environmental variables can reflect population trends measured in other ways, and that one can begin to make inferences about population trends across remote interior Australia using modelling approaches such as those developed here. For shorebirds, these models helped improve our estimates of total population size, which has been the foundation on which abundance thresholds to identify important habitats have been based (DEH, 2006;Clemens et al, 2010). Model predictions also indicated that over the decades some species experience periods of far greater contractions in suitable habitat than others, consistent with other recent work (Runge et al, 2015a).…”
Section: Discussionsupporting
confidence: 65%
“…Existing metrics on the importance of a wetland for shorebirds rely on counts of the number of birds that use the habitat (DEWHA, 2009;Clemens et al, 2010), but high spatial and temporal variation in the availability of ephemeral habitats has left no clear understanding of how, where or when to take conservation action related to ephemeral wetlands that would be sufficient to protect these species. As Piersma (2007) points out, people throughout the globe are conducting unintended massive scale experiments on the impacts of habitat loss and degradation on shorebird populations.…”
Section: The Importance Of Conserving Migratory and Highly Mobile Spementioning
confidence: 99%
“…Models generally predicted habitat in areas characterized by wide sandy beaches or overwash fans, with sparse vegetation and access to low-energy shorelines (Maslo, Leu, et al, 2016;. The similarity in model predictions when viewed as a binary value and not a raw probability value underscores the importance of the selection and application of suitability threshold values in species distribution and other habitat models (Clemens, Weston, Haslem, Silcocks, & Ferris, 2010). When viewed as a binary measure of suitability, we observed core areas of habitat predicted by both models (e.g., Figure 3-5; and 196.3 ha of habitat in the New Jersey and New York study areas, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that in protected habitats, plants and animals are more than twice as likely to move toward recovery as species in unprotected habitats (Myers, 1988;Myers et al, 2000). However, identifying critical habitats and hotspots remains highly challenging because the comprehensive data on species distribution and abundance that are required for such identification are often lacking (Clemens, Weston, Haslem, Silcocks, & Ferris, 2010;Clemens, Herrod, & Weston, 2014). To overcome this limitation, species distributions are predicted by either (1) associating individual species occurrences with known habitat preferences, constructing relationships between environments and species distribution at the individual species level, and then combining distribution information from different species (Austin, 2002;Elith et al, 2006;Araújo & New, 2007;Elith & Leathwick, 2009) or (2) using a cross-covariance matrix to find linear combinations of environments and a group of species' distributions that have a maximum correlation with each other at the community level Johnson & Wichern, 2007).…”
Section: Introductionmentioning
confidence: 97%